The anthropological passivity of guilt : A study of mankind and the dimension of the aperture towards salvation - Fuster Camp, Ignasi (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
This article tries to explore the line of passivity —or redundancy— of guiltiness in the human being. The existential question is the possibility of overcoming guilt. Therefore, we explore and analyse the diverse anthropological moments generated by guilt: the feeling of guilt and the human repentance. There is a privileged experience to overcoming guilt: human forgiveness. Finally, we face the anthropological act of forgiveness: its possibilities, its truth and its limits.